Synthesis and antitubercular activity of new benzo[b]thiophenes - Mahajan, Pravin S.; Nikam, Mukesh D.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman; Gill, Charansingh H. (ACS Medicinal Chemistry Letters, 2016)
In vitro and ex vivo efficacies of four series of benzo[b]thiophene-2-carboxylic acid derivatives were studied against Mycobacterium tuberculosis H37Ra (MTB). Benzo[b]thiophenes were also tested in vitro against multidrug resistant Mycobacterium tuberculosis H37Ra (MDR-MTB), and 7b was found to be highly active against A- and DMDR-MTB/MTB (MIC ranges 2.73-22.86 mu g/mL). The activity of all benzo[b]-thiophenes against M. bovis BCG (BCG) was also assessed grown under aerobic and under conditions of oxygen depletion. Compounds 8c and 8g showed significant activity with MICs of 0.60 and 0.61 mu g/mL against dormant BCG. The low cytotoxicity and high selectivity index data against human cancer cell lines, HeLa, Panc-1, and THP-1 indicate the potential importance of the development of benzo[b]thiophene-based 1,3-diketones and flavones as lead candidates to treat mycobacterial infections. Molecular docking studies into the active site of DprE1 (Decaprenylphosphoryl-beta-n-ribose-2'-epimerase) enzyme revealed a similar binding mode to native ligand in the crystal structure thereby helping to understand the ligand protein interactions and establish a structural basis for inhibition of MTB. In summary, its good activity in in vitro and ex vivo model, as well as its activity against multidrug-resistant M. tuberculosis H37Ra in a potentially latent state, makes 7b an attractive drug candidate for the therapy of tuberculosis.
Keywords: Benzo[b]thiophene; Cytotoxicity; M. Bovis BCG; MDR-MTB; Molecular docking

Synthesis, biological evaluation and molecular docking studies of N-acylheteroaryl hydrazone derivatives as antioxidant and anti-inflammatory agents - Mahajan, Pravin S.; Nikam, Mukesh D.; Khedkar, Vijay M.; Jha, Prakash C.; Sarkar, Dhiman; Gill, Charansingh H. (Research on Chemical Intermediates, 2016)
In search of new therapeutics with greater potency, three new series of 3-methyl-1-phenyl-1H-thieno[2,3-c]pyrazole-5-carbohydrazide derivatives have been synthesized and evaluated for their in vitro antioxidant and anti-inflammatory activities. The hydrazones bearing a core pyrazole, chromone and tetrazolo[1,5-a]quinoline scaffold showed promising activities. Interestingly, compounds 3a (EC50 = 06.00 +/- A 2.36) and 5c (EC50 = 07.21 +/- A 0.67) showed the most potent antioxidant activity, while compounds 3a (EC50 = 10.25 +/- A 1.08), 7b (EC50 = 10.50 +/- A 0.99) and 7c (EC50 = 11.18 +/- A 0.15) showed significant anti-inflammatory activity. Furthermore, molecular docking studies also revealed a significant correlation between the binding score and biological activity for these compounds to describe the molecular basis for the structure activity relationship (SAR) results. As these compounds are good cyclooxygenase inhibitors, isoenzyme inhibitory potency studies are warranted.
Keywords: Anti-inflammatory; Antioxidant; Docking study; N-Acylhydrazones; Structure-activity relationship